2022
DOI: 10.1073/pnas.2116662119
|View full text |Cite
|
Sign up to set email alerts
|

The m 6 A reader YTHDC2 is essential for escape from KSHV SOX-induced RNA decay

Abstract: The role of N6-methyladenosine (m6A) modifications has increasingly been associated with a diverse set of roles in modulating viruses and influencing the outcomes of viral infection. Here, we report that the landscape of m6A deposition is drastically shifted during Kaposi’s sarcoma–associated herpesvirus (KSHV) lytic infection for both viral and host transcripts. In line with previous reports, we also saw an overall decrease in host methylation in favor of viral messenger RNA (mRNA), along with 5′ hypomethylat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…Interestingly, this effect can still be observed when accounting for the nucleotide composition of the genomes and hence taking into account the high GC content of some alphaherpesviruses, such as PRV and HSV-1 ( Figure S5 ). Of additional interest, the latter analysis shows a significant enrichment of the DRACH motif in the genomes of gammaherpesviruses, in line with the notion that viral transcripts of different members of this herpesvirus subfamily are m6A methylated, which is thought to be important for different aspects of the biology of these viruses ( Tan et al, 2017 ; Ye et al, 2017 ; Hesser et al, 2018 ; Baquero-Perez et al, 2019 ; Lang et al, 2019 ; Dai et al, 2021 ; Tang et al, 2021 ; Xia et al, 2021 ; Zheng et al, 2021 ; Macveigh-Fierro et al, 2022 ).…”
Section: Resultssupporting
confidence: 69%
“…Interestingly, this effect can still be observed when accounting for the nucleotide composition of the genomes and hence taking into account the high GC content of some alphaherpesviruses, such as PRV and HSV-1 ( Figure S5 ). Of additional interest, the latter analysis shows a significant enrichment of the DRACH motif in the genomes of gammaherpesviruses, in line with the notion that viral transcripts of different members of this herpesvirus subfamily are m6A methylated, which is thought to be important for different aspects of the biology of these viruses ( Tan et al, 2017 ; Ye et al, 2017 ; Hesser et al, 2018 ; Baquero-Perez et al, 2019 ; Lang et al, 2019 ; Dai et al, 2021 ; Tang et al, 2021 ; Xia et al, 2021 ; Zheng et al, 2021 ; Macveigh-Fierro et al, 2022 ).…”
Section: Resultssupporting
confidence: 69%
“…m6A readers, such as YTH-domain family proteins, have been proved to modulate gene expression via recognizing m6A-transcripts, and both the YTHDC1 and YTHDC2 were associated with methylated mRNA stability. 39,40 Via bioinformatics analysis, we identified that YTHDC2 interacted with ASH1L mRNA, and that the binding site of YTHDC2 overlapped with the m6A site of ASH1L mRNA, suggesting that YTHDC2 might participate in the regulation of ASH1L expression. By recognizing the m6A site, YTHDC2 sustained CYLD mRNA stability in lung cancer cells 41 and protected IL-6 mRNA from SOX degradation during KSHV lytic infection.…”
Section: Discussionmentioning
confidence: 95%
“…In other studies, YTHDC2 has been shown to regulate the translation of some genes, such as IGF1R and HCV, by eliminating the secondary structure of its mRNA [4,11,14]. On the other hand, some studies reported that YTHDC2 is also involved in the stability of m 6 A-modified mRNAs, such as meiosis-related genes and interleukin-6 gene [26,27]. m 6 A modification has been found in SOX2, c-MYC, and NANOG mRNAs and is thought to regulate the stabilization/destabilization and translation of them [28][29][30].…”
Section: Discussionmentioning
confidence: 99%